Recognizing the Costs of Teen Pregnancy: “Baby Think it Over” - A. Weiss Josie; Gattamorta Karina; Davis Shelina; Chabot Danielle (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
Despite recent improvements in teen pregnancy and birth rates, 2000 teens get pregnant each day in the U.S. Innovative strategies that are effective and acceptable within communities are needed to continue these declines in teen pregnancies. Captivating educational interventions enhanced by infant simulators, such as “Baby Think it Over” (BTIO), can discourage teen pregnancy. The purpose of this research was to evaluate a BTIO intervention to determine the effectiveness of the program in changing 236 high school students’ perceptions of the costs of teen parenting. From a comparison of pre-test/two post-test measures, it appears the participants recognized that teen parenting would be costly in terms of increased difficulty in making responsible decisions as well as the challenges of juggling school with parenting. They also recognized other costs including negative impacts on relationships, on feelings of personal worth, and the likelihood of diminished achievements in the future.
Keywords: prevention